Development of Problem-Based Learning E-Module Assisted by Scratch Interactive Media for Grade VII Students of Maitreyawira Private Junior High School Deli Serdang - Siti Mawarni Pohan; Abdul Hasan Saragih; Sugiharto Sugiharto (CV. Media Inti Teknologi, 2026)
Background: Modern education emphasizes competencies in critical thinking, creativity, communication, and collaboration, requiring adaptive models and learning media. At Maitreyawira Deli Serdang Private Junior High School, incompatible textbooks and media in Social Studies have resulted in low student learning outcomes.Aims: This research aims to develop a Problem-Based Learning assisted by Scratch Interactive to address these challenges.Methods: Utilizing the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), this study involved 30 students from class VII-E. Data were collected using feasibility questionnaires validated by six expert reviewers (2 media, 2 design, 2 material experts), a practicality questionnaire for students, and pre-test/post-test instruments to measure effectiveness. Data were analyzed using quantitative and qualitative descriptive techniques.Results: The validation tests revealed high feasibility: 88.71% (very valid) for material, 93.85% (very valid) for learning design, and 78.46% (valid) for media. The practicality test achieved 92.33% (very practical). Furthermore, the effectiveness test showed a significant increase from a pre-test score of 55.33% to a post-test score of 81.00%, supported by an N-Gain value of 0.51 (moderate improvement category).Conclusion: The PBL-based E-Module assisted by Scratch is proven to be valid, practical, and effective in improving seventh-grade students' understanding of Social Studies.